(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Sports participation has an important role to play. Sports activities are change environment to another. Also, using information and communication technology such as distance learning has become a rapidly growing trend. Online delivery platform becomes very important methods for the graduate and undergraduate students to achieves the advanced degrees and knowledge.The aim of this study to investigate the impact of online learning on Sports participation during pandemic (COVID-19). Methods: This study usedthe previous studiesto investigate theuse of online learning on Sports participation during pandemic (COVID-19). This research uses different databased such as Science direct, Google Scholar, Scopus and other databases. Results: This study comeswith some obstacles that face student in Saudi Arabia to practise the sport activities during the pandemic (COVID-19). Those obstacles should consider by Saudi ministry of education.